Conscious sedation for balloon mitral valvuloplasty - Sharma, Bharati Devi; Deo, Gopendra Prasad; Shrestha, Indra Narayan; Regmi, Shyam Raj (Journal of Chitwan Medical College, 2018)
Introduction: Analgesia and sedation are required for the comfort of patient and the cardiologist during Balloon mitral valvotomy. Efficacy of analgesia, sedation, and patient satisfaction with conscious sedation and local anesthesia was compared with local anaesthesia only during procedure. Methods: This was single-centered, prospective study conducted in Chitwan Medical College. All 66 patients, who underwent Balloon mitral valvotomy from February 2015 to January 2017, were enrolled in this study. They were divided into two groups by computer generated randomization. Thirty three patients received bolus injection fentanyl 1 mcg/kg and injection midazolam bolus 0.02 mg/kg along with local anaesthesia (20ml xylocaine) at femoral puncture site and other 33 patients received local anaesthesia only. Pain intensity (by visual analog score), anxiety score, overall patient and operator’s satisfaction, and effect on cardio respiratory parameters were assessed. Student’s unpaired t-test was applied. P < 0.05 was considered statistically significant. Results: Both the groups were comparable with respect to age, gender and pre and post balloon mitral valvotomy mitral valve area. Statistically significant difference was found with respect to anxiety score (1.1 + 0.43 Vs. 1.99 + 0.01), VAS score (operator’s opinion) (9.10 + 0.56 Vs. 7.53 + 1.01) and VAS score (patient’s opinion) (8.54 + 0.87 Vs. 5.55 + 1.14). Fall in systolic pressure, diastolic blood pressure, mean arterial blood pressure, and respiratory rate was found in fentanyl group, but the values were within normal limits and statistically not significant. Conclusion: Conscious sedation with bolus dose of fentanyl and midazolam with local anesthesia at puncture site is better than only local anesthesia during balloon mitral valvotomy procedure to relieve patient’s anxiety and to improve patient’s and operator’s comfort without affecting hemodynamic parameters.